Peningkatan Resilisensi Pekerja Informal Wanita Dalam Menghadapi Situasi Pandemi - Mohammad Abu Suhud; Beti Nur Hayati (Yayasan Sagita Akademia Maju, 2025)
The global economic crisis in recent years has had a significant impact on the informal sector, especially female workers. This has resulted in income reductions, disruptions in distribution, and increasing psychological pressures. Many women who depend on the informal sector face major challenges in maintaining their economic and mental well-being. To address this issue, a community service program is needed to enhance the resilience of informal workers. This program is designed to strengthen skills through lectures and tutorials, covering strategies for survival in the informal sector, stress management, product innovation, and the use of digital marketing. Through this program, it is hoped that female informal workers will not only be able to face existing challenges but also acquire skills that will help them develop their businesses independently. With the skills they gain, they are expected to compete in a broader market and run more sustainable businesses in the future. This program aims to have a long-term impact by strengthening the local economy and improving the quality of life for female informal workers